Pengembangan Aplikasi Berbasis Website untuk Efisiensi dalam Pengumpulan Dokumen Tugas Akhir dan Kerja Praktik Mahasiswa D3 Teknik Informatika UKSW - Adi Hendra Kristanto; Sri Winarso Martyas Edi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Final Projects (TA) and Internships (KP) are essential requirements for students, particularly in the Diploma (D3) Informatics Engineering Program at UKSW, as they are mandatory for graduation. However, the document management process for TA and KP still faces several challenges, such as the absence of an integrated system, difficulties in monitoring document status, and communication that is still conducted manually, which hinders academic administrative processes. Therefore, this study aims to design and develop a web-based repository system for managing Final Project and Internship documents. The system was developed using the Waterfall method, with a design approach based on UML and implementation using the Laravel framework and MySQL database. System testing was conducted through black-box testing, performance testing, and User Acceptance Testing (UAT) involving users. The results show that the developed system improves the efficiency of the document submission process by 49.8% compared to the previous method. In addition, UAT results indicate a very high level of user acceptance, with average scores of 4.3 for students and 4.5 for supervisors. Usability testing using the System Usability Scale (SUS) also yielded a score of 82.88, indicating a high level of system usability. Therefore, the developed system not only addresses issues in managing TA and KP documents but also enhances efficiency, transparency, and the quality of interaction between students and supervisors.